2018
DOI: 10.1002/2017gl076916
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Internal Tides Over a Shallow Ridge Investigated With a High‐Resolution Downscaling Regional Ocean Model

Abstract: This study investigates the dynamics of tidally induced internal waves over a shallow ridge, the Izu‐Ogasawara Ridge off the Japanese mainland, using a downscaled high‐resolution regional ocean numerical model. Both the Kuroshio and tides contribute to the field of currents in the study area. The model results show strong internal tidal energy fluxes over the ridge, exceeding 3.5 kW m−1, which are higher than the fluxes along the Japanese mainland. The flux in the upstream side of the Kuroshio is enhanced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…It would also be interesting to examine how ocean mixing in a more realistic 3D environment would affect zooplankton dispersion. Although 3D simulations can provide further details of physical processes, the primary internal wave dynamics are similar for both 2D and 3D simulations (see Masunaga et al 2018Masunaga et al , 2019.…”
Section: Limitationsmentioning
confidence: 99%
“…It would also be interesting to examine how ocean mixing in a more realistic 3D environment would affect zooplankton dispersion. Although 3D simulations can provide further details of physical processes, the primary internal wave dynamics are similar for both 2D and 3D simulations (see Masunaga et al 2018Masunaga et al , 2019.…”
Section: Limitationsmentioning
confidence: 99%
“…In addition, recent studies have suggested that tidal forcing noticeably influences the current and eddy field by modification of the kinetic energy flux via internal waves [e.g. Masunaga et al 2018;32]. To investigate the effect of downscaling and tidal variability on oceanic flow, eddies, and the resultant radionuclide distribution, we conducted statistical analyses by using the results obtained using the four models over the period between January 22 and 1 February 2016.…”
Section: Effects Of Downscaling and Tidementioning
confidence: 99%
“…Tidal forcing is a major contributor to internal waves, and internal waves with tidal frequencies are called internal tides. The interaction of the tidal flow and shallow ridges/sills is one of the major factors contributing to internal tide generation (Alford et al 2015;Da Silva et al 2015;Masunaga et al 2018). The energy of internal waves increases when the topographic slope angle matches the beam angle of internal waves known as the critical slope (Cacchione et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Internal waves transport energy from generation sites and finally break, inducing turbulence and mixing. Shoreward propagating internal waves increase their nonlinearity and generate strong turbulent mixing on shallow slopes (Richards et al 2013;Masunaga et al 2015), occasionally causing sediment resuspension and mass transport (Masunaga et al 2017a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation